A geographical analysis of agricultural land uses for field crops in Khalis for the agricultural season (2020-2021) - FALIH, OMAR ABDULRASOOL (Al-Adab Journal, 2023)
The topic of studying the uses of agricultural land has taken the interest of many geographers recently, as it is included in the geographical analyzes that explain the nature of the agricultural process in the area to be studied, to reach the optimal investment of agricultural land according to the existing data, whether nature or human. Through the study of field crops in the study area, it was found that the economically feasible field crops are (wheat, barley, yellow corn, rice) distributed according to administrative units with great variation in terms of production and cultivated area.